SLR Analysis Of The Influence Of Digital Transformation On MSMe Performance With Business Model Innovation As A Moderating Variable - Andi Hassan Zada Islamie; Anjar Priyono (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the impact of digital transformation on the performance of MSMEs, with business model innovation serving as a moderating variable, in Sleman Regency, Special Region of Yogyakarta. A total of 118 MSME actors in the region participated as respondents, with data collected through questionnaires and analyzed using the SmartPLS 3 application and a convenience sampling method. The findings reveal that digital transformation has a positive impact on MSME performance, digital transformation also positively influences business model innovation, business model innovation significantly affects MSME performance, and business model innovation moderates the relationship between digital transformation and MSME performance. These results can serve as a reference for MSME practitioners in optimizing digital transformation and business model innovation to enhance their business performance.